2017
DOI: 10.2463/mrms.mp.2015-0161
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Computed Diffusion Weighted Imaging and Optimization of b-value in Cervical Cancer

Abstract: Purpose:To evaluate the feasibility of computed diffusion weighted imaging (DWI) in cervical cancer and investigate the optimal b-value using computed DWI.Methods:The present retrospective study involved 85 patients with cervical cancer in the International Federation of Gynecology and Obstetrics (FIGO) stage IB, IIA or IIB. DWI was obtained with b-values of 0, 100, 500 and 1000 s/mm2. Computed DWI with b-values of 800, 1000, 1300, 1600 and 2000 s/mm2 (cDWI800, cDWI1000, cDWI1300, cDWI1600, cDWI2000) were gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Different b‐values for breast DWI have been compared by O'Flynn et al; however, in their study only images from b‐values of 1500 and 2000 s/mm 2 were calculated and these performed equally in terms of image quality . Lesion visibility and image quality were rated best at intermediate b‐values (1300 and 1600 s/mm 2 ) in a study on cervical cancer, while in the prostate, optimal b‐values were reported to range between 1500–2500 s/mm 2 , and 2000–3000, respectively …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different b‐values for breast DWI have been compared by O'Flynn et al; however, in their study only images from b‐values of 1500 and 2000 s/mm 2 were calculated and these performed equally in terms of image quality . Lesion visibility and image quality were rated best at intermediate b‐values (1300 and 1600 s/mm 2 ) in a study on cervical cancer, while in the prostate, optimal b‐values were reported to range between 1500–2500 s/mm 2 , and 2000–3000, respectively …”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the results of this study, as well as those of a phantom study published in 2011, show that this is also true for calculated b‐values: tissue SI will decrease heavily with increasing b‐values; diffusion‐restricted, water‐containing tumors such as most breast cancers will lose less signal; and background noise will increase. Similar results using calculated b‐values have been reported, eg, in cervical cancer …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed DWI (cDWI) is a mathematical computation method that generates higher b‐value DWIs from images acquired with lower b‐values . It was reported that cDWI could obtain good image quality and a high contrast‐to‐noise ratio (CNR) by suppressing background signal and, thus, might increase lesion conspicuity . In the detection of breast cancer, it has been shown that cDWI with a higher b‐value has the potential to improve diagnostic sensitivity .…”
mentioning
confidence: 99%
“…10 It was reported that cDWI could obtain good image quality and a high contrast-to-noise ratio (CNR) by suppressing background signal and, thus, might increase lesion conspicuity. [11][12][13][14] In the detection of breast cancer, it has been shown that cDWI with a higher bvalue has the potential to improve diagnostic sensitivity. 15 However, as b-value increases, the signal intensity decreases in all tissues.…”
mentioning
confidence: 99%